Vedic Aryan Society and Pattern of Production System (Paramita: Historical Studies Journal, 2020)
History is the sequential chain of the social structure of human beings. The Vedic Aryan society represents ancient human society. The main objective of this article is to find out the production system of livelihoods and the source of the means of production adopted by the Vedic Aryans. Based on historical facts of ancient civilization obtained through secondary sources, which have been analyzed through historical content analysis method. An attempt has been made in this article to find out the method of production of livelihoods and the source of production adopted by the Vedic Aryans. Men to be more involved in the expansion of resources and livestock and agricultural land, and as women were managing domestic work, the ownership of men over resources increased. Due to the process of state-building, regarding the ownership of resources, it appears that the resources were in the collective right of the family and couldnâ€™t be sold or bought without the permission of the head of the family. We concluded that Mentioned facts are analog to the theory of production system of Karl MarxÂ Sejarah adalah rantai sekuensial dari struktur sosial manusia. Masyarakat Arya Weda mewakili masyarakat manusia purba. Tujuan utama artikel ini adalah untuk mengetahui sistem produksi mata pencaharian dan sumber alat produksi yang diadopsi oleh Arya Weda. Berdasarkan fakta sejarah peradaban kuno diperoleh melalui sumber-sumber sekunder yang dianalisis melalui metode analisis isi sejarah. Sebuah upaya telah dilakukan dalam artikel ini untuk mengetahui metode produksi mata pencaharian dan sumber produksi yang diadopsi oleh para Arya Weda. Laki-laki untuk lebih terlibat dalam perluasan sumber daya dan ternak serta lahan pertanian, dan ketika perempuan mengelola pekerjaan rumah tangga, kepemilikan laki-laki atas sumber daya meningkat. Dalam proses pembangunan negara, mengenai kepemilikan sumber daya, tampak bahwa sumber daya tersebut merupakan hak kolektif keluarga dan tidak dapat dijual atau dibeli tanpa izin kepala keluarga. Kami menyimpulkan bahwa fakta yang disebutkan adalah analog dengan teori sistem produksi Karl MarxÂ